The type of exposure interferes with the compatibility of herbicides with Metarhizium rileyi? (Research, Society and Development, 2020)
Therefore, this study aimed to assess the direct and indirect effect of some herbicides used in the management of soybeans with the fungus entomopathogenic M. rileyi. The herbicides used in the tests were: Aramo®, Basagran®, Flex® and Glyphosate®, a minimum and maximum, when possible doses. Experiments were conducted in two differents methods, the products were first mixed with the culture medium Potato Dextrose Agar (PDA) and then still liquid inoculation of the fungus was made. The second form after the nutritive medium is being poured and solidified, the applications of fungicides with the aid of a Potter tower and pathogen inoculation, which occurred were made in two ways: first the product in their respective doses and subsequently the pathogen; and the pathogen and then the product. We evaluated germination, vegetative growth and conidia production through direct and indirect exposure of the same grout containing products. Only Basagran® (minimum dose) and Flex® products were compatible with M. rileyi Basagran® the product at the maximum dose was moderately toxic and other products and doses were toxic, these results were observed for M. rileyi in direct and indirect exposure to inoculation before and after application. There weren’t differences between the methodologies to classify the toxicology of the product.